Phallus campanulatus Berk. (Phallaceae, Agaricomycetes), a poorly known species from South America and its synonym P. granulosodenticulatus B. Braun - Trierveiler-Pereira, Larissa; Baltazar, Juliano M.; Silveira, Rosa Mara B. Da (Phytotaxa, 2016)
Phallus campanulatus and P. granulosodenticulatus are two fungal species proposed in 1842 and 1932, respectively, based on specimens collected on sandy soil in South America. Studies on recently collected specimens and herbaria material lead us to conclude that they are the same species. Therefore, the synonymy of P. granulosodenticulatus under P. campanulatus is proposed. Additionally, a lectotype is selected for P. granulosodenticulatus.